2016
DOI: 10.3389/fbioe.2016.00020
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Investigation on the Use of Closed-Loop Electrical Stimulation to Assist Individuals with Stroke to Perform Fine Movements with Their Hemiparetic Arm

Abstract: Stroke is the leading cause of upper limb impairments resulting in disability. Modern rehabilitation includes training with robotic exoskeletons and functional electrical stimulation (FES). However, there is a gap in knowledge to define the detailed use of FES in stroke rehabilitation. In this paper, we explore applying closed-loop FES to the upper extremities of healthy volunteers and individuals with a hemiparetic arm resulting from stroke. We used a set of gyroscopes to monitor arm movements and used a non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Makowski et al (42) and Lew et al (43) studied different reaching movements and ADLs in chronic stroke patients, via the application of FES. The results they obtained showed improvements in range distances, hand opening, an increase in forearm muscle activity, and the ability to complete ADLs in which shoulder flexion was required and in which elbow extension was required and which the patients were initially unable to perform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Makowski et al (42) and Lew et al (43) studied different reaching movements and ADLs in chronic stroke patients, via the application of FES. The results they obtained showed improvements in range distances, hand opening, an increase in forearm muscle activity, and the ability to complete ADLs in which shoulder flexion was required and in which elbow extension was required and which the patients were initially unable to perform.…”
Section: Discussionmentioning
confidence: 99%
“…In stroke subjects, the application of electrostimulation to the muscles of the UL has been found to enhance the reacquisition of motor skills with the affected UL and to increase the degree of shoulder flexion and elbow extension, thus assisting the reaching movement, as measured with motion analysis systems; our results confirm and extend these previous works ( 42 44 ) by demonstrating that FES applied to the UL muscles is effective for improving simple single joint movements as well as more complex reach-to-grasp movements performed with the hemiparetic UL. Makowski et al ( 42 ) and Lew et al ( 43 ) studied different reaching movements and ADLs in chronic stroke patients, via the application of FES. The results they obtained showed improvements in range distances, hand opening, an increase in forearm muscle activity, and the ability to complete ADLs in which shoulder flexion was required and in which elbow extension was required and which the patients were initially unable to perform.…”
Section: Discussionmentioning
confidence: 99%
“…In order to align with principles known to drive functional recovery, notably the need to intensively practise a variety of challenging, functional tasks, 3,4 and offer sufficient flexibility to accommodate a broad range of patients, FES devices are becoming increasingly sophisticated. These advanced FES devices have multiple channels, are usually controlled via sensors, provide some form of biofeedback and may incorporate electrode arrays 2,5 Although largely unreported, an unintended consequence of this increase in complexity is likely to have been an increase in setup time of some of these devices. For instance, systems that include a brain interface require calibration of the interface, and some of the recent upper limb systems based on iterative learning control rely on person-specific dynamic model identification.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we can design our training platform fully via functional electrical stimulation. However, Lew et al reported that not all individuals with chronic stroke are able to use an FES unit for elbow position control (Lew et al, 2016 ). Therefore, we did not use a full FES design in this study.…”
Section: Methodsmentioning
confidence: 99%